Smokers run increased risk of developing anti-natalizumab antibodies. (July 2014) - Hedström, AK; Alfredsson, L; Lundkvist Ryner, M; Fogdell-Hahn, A; Hillert, Jan; Olsson, T
Background: Smoking may contribute to the induction of neutralizing antibodies to interferon β-1a. Objective: In this study, we aimed to investigate the influence of smoking on the risk of developing antibodies to natalizumab, another biological drug in the treatment of multiple sclerosis. Methods: This report is based on 1338 natalizumab-treated multiple sclerosis patients included in either of two Swedish case-control studies in which information on smoking habits was collected. Using logistic regression, patients with different smoking habits were compared regarding risk of developing anti-natalizumab antibodies, by calculating odds ratios with 95% confidence intervals. Results: Compared with nonsmokers, the odds ratio of developing anti-natalizumab antibodies was 2.4 (95% CI 1.2–4.4) for patients who smoked at the time of screening, and a significant trend showed higher risk of developing antibodies with higher intensity of smoking. When smoking within two years prior to screening was considered, the odds ratio of developing anti-natalizumab antibodies was 2.7 (1.5–5.1). Interpretations: The finding strengthens our hypothesis of the lungs as immune-reactive organs on irritation in relation to autoimmune responses, and may also be of clinical relevance since antibodies against natalizumab abrogate the therapeutic effect of the treatment.